Evaluation of efficacy of immunotherapy in children with asthma monosensitized to Alternaria - Kılıç, Mehmet; Altıntaş, Derya Ufuk; Yılmaz, Mustafa; Bingöl-Karakoç, Gülbin; Burgut, Refik; Güneşer-Kendirli, Seval (The Turkish Journal of Pediatrics, 2011)
In this study, we aimed to evaluate the efficacy of specific immunotherapy (SIT) in children monosensitized to Alternaria. Sixteen children with bronchial asthma monosensitized to Alternaria were enrolled in the study. Patients were divided into two groups as the immunotherapy group (Group I; 9 patients) and control group (Group II; 7 patients). A significant reduction in bronchial responsiveness to methacholine and Alternaria was found in Group I after one year of SIT (p = 0.03, p = 0.006) in comparison to controls. Specific IgE levels were decreased in the immunotherapy group (p = 0.001). Following allergen provocation, a rise in sputum eosinophil count was found to be lower in the SIT group compared to controls after one year (p = 0.011), and sputum eosinophil cationic protein (ECP) levels did not change in the SIT group, while there was a statistically significant increase in controls. Our results demonstrated that SIT with Alternaria caused clear changes in airway responsiveness and serum-specific IgE levels. However, further long-term studies in large series should be carried out for clinical documentation of the efficacy of SIT in the treatment of children with Alternaria allergy.